Addressing psychosocial needs in patients with Long-COVID (PsyLoCo-Study): study protocol of a pilot-study of a specialized modular intervention - Allwang, Christine; Frank, Tamara; Bruckmann, Paul; Dinkel, Andreas; Binneboese, Marius; Wallis, Hannah; Elgner, Melanie; Giel, Katrin E.; Schurr, Marisa; Gündel, Harald; Wedekind, Lisa; Kuhn, Julia; et al. (Frontiers in Psychiatry, 2024)
After an acute infection with the corona virus 10-20% of those affected suffer from ongoing or new symptoms. A causal therapy for the phenomenon known as Long-/Post-COVID is still lacking and specific therapies addressing psychosocial needs of these patients are imperatively needed. The aim of the PsyLoCo-study is developing and piloting a psychotherapeutic manual, which addresses Long/Post-COVID-related psychosocial needs and supports in coping with persistent bodily symptoms as well as depressive or anxiety symptoms.This pilot trial implements a multi-centre, 2-arm (N=120; allocation ratio: 1:1), parallel group, randomised controlled design. The pilot trial is designed to test the feasibility and estimate the effect of 1) a 12-session psychotherapeutic intervention compared to 2) a wait-list control condition on psychosocial needs as well as bodily and affective symptoms in patients suffering from Long/Post-COVID. The intervention uses an integrative, manualized, psychotherapeutic approach.The primary study outcome is health-related quality of life. Outcome variables will be assessed at three timepoints, pre-intervention (t1), post-intervention (t2) and three months after completed intervention (t3). To determine the primary outcome, changes from t1 to t2 are examined. The analysis will be used for the planning of the RCT to test the efficacy of the developed intervention.• Discussion:The pilot study will evaluate a 12-session treatment manual for Long/Post COVID sufferers and the therapy components it contains.The analysis will provide insights into the extent to which psychotherapeutic treatment approaches improve the symptoms of Long/Post COVID sufferers. The treatment manual is designed to be carried out by psychotherapists as well as people with basic training in psychotherapeutic techniques. This approach was chosen to enable a larger number of practitioners to provide therapeutic support for Long/Post COVID patients. After completion of the pilot study, it is planned to follow up with a randomized controlled study and to develop a treatment guideline for general practitioners and interested specialists.